Internal and external auditor coordination for corporate governance / Hari Ramulu a/l Munusamy - Munusamy, Hari Ramulu (2005)
Corporate collapses and others damaged the credibility of most companies in the United States, Europe and Malaysia. To help restore confidence, US Congress passed the SARBANES OXLEY ACT 2002 (SOA) and Malaysia introduced the AUDIT COMMITTEE through Malaysian Institute of Corporate Governance (MICG) in March 1998. Both - SOA and MICG, mandate new requirements for the reporting of business results, consequently increasing the scope of work performed by the external auditor. Since, the new responsibilities of the external auditors have grown, internal auditors have the opportunity to add value to their organisation through improved coordination with the external auditors. This paper examines how internal auditors can add value by coordinating through external auditors, the reasons for coordinating with the external auditor, how the coordination may best be achieved, and the steps internal auditors should take to facilitate the coordination effort.